Reconstruction of a short tibia stump after forced shortening with subsequent lengthening using the Ilizarov method - Yurii Oleksiiovych Bezsmertnyi; Viktor Ivanovych Shevchuk; Olexander Yuriyovych Branitsky; Olexander Yuriyovych Bezsmertnyi; Dmytro Vadymovych Bondarenko (Medicinski glasnik, 2026)
Aim: To demonstrate the possibilities of reconstructing a prosthetic stump in a complex defect using staged osteotomy and lengthening, since for successful prosthetic replacement of the tibial stump, its sufficient length is necessary, which is not always possible. Methods: In this article, we present a 25-year-old man diagnosed with a non-prosthetic short stump of the right tibia with extensive necrotized scars of the anterior and end surfaces, closely soldered to the bone sawdust, which underwent lengthening of the short stump of the tibia using the Ilizarov method. Results: The uniqueness of the performed operation is the shortening of the tibia along with the removal of pathologically altered tissues, the formation of a stump, osteotomy of the tibial stump with its subsequent lengthening.Thereconstructionlasted 105 days (5 daysoffixation, 25 daysoflengthening, 75 daysoffixation), whichallowedtoobtain a functionalstump. Conclusions: A stump was created that provided functional prosthetics. We believe that the technique can be successfully used in young people even in the absence of soft tissue reserve of the stump.
Keywords: аmputation; Ilizarov technique; myocutaneous flap; osteotomy; tibia